(untitled) (Research, Society and Development, 2021)
The absence of an eyeball results in physical, psychosocial and functional alterations on an individual. Therefore, rehabilitation procedures are essential to repair the patient’s self-esteem, self-confidence and physiological features. The aim of this study is to describe a case of ocular prosthetic rehabilitation in a pediatric patient. A female teenager, 17 years old, was referred to the maxillofacial prosthetic clinic to replace her former prosthesis fabricated two years ago. The new ocular prosthesis was confectioned with termopolymerizable acrylic resin and hand painted with acrylic paint on a colorless acrylic ocular bottom. The prosthesis was installed and the instructions were explained. In teenage patients the prothesis must be elaborated as soon as possible with periodic replacements in accordance with the growth period. The awareness of legal guardians and patients is essential to the success of the treatment in pediatric patients. In the present case, the patient was satisfied with the aesthetic and functional outcome.